2019
DOI: 10.1001/amajethics.2019.1089
|View full text |Cite
|
Sign up to set email alerts
|

What Should Clinicians Do to Engage the Public About Gene Editing?

Abstract: Genome editing holds tremendous promise for preventing, ameliorating, or even curing disease, but a thorough discussion of its bioethical and social implications is necessary to protect humankind against harm, a central tenet of the original Hippocratic Oath. It is therefore essential that medical students, physicians, and all health care workers have a working understanding of what gene editing entails, the controversy surrounding its use, and its far-reaching clinical and ethical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Patient populations can be especially vulnerable to promise of the benefits of gene editing made in the media and consequently, patients may act on this distorted information. Thus, it is important that healthcare providers are sufficiently prepared to correct any misinformation and explain the current state of germline gene editing for the patient's genetic condition in ways that are accessible to patients, their families, and other relevant stakeholders (Alsaigh, Nicholson, and Topol 2019;Meagher et al 2020). In a recent study, genetic professionals reported experiencing feelings of anxiety due to having insufficient methods to evaluate the success of a future modification and the undetermined risk of adverse effects due to the modification (Taguchi et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Patient populations can be especially vulnerable to promise of the benefits of gene editing made in the media and consequently, patients may act on this distorted information. Thus, it is important that healthcare providers are sufficiently prepared to correct any misinformation and explain the current state of germline gene editing for the patient's genetic condition in ways that are accessible to patients, their families, and other relevant stakeholders (Alsaigh, Nicholson, and Topol 2019;Meagher et al 2020). In a recent study, genetic professionals reported experiencing feelings of anxiety due to having insufficient methods to evaluate the success of a future modification and the undetermined risk of adverse effects due to the modification (Taguchi et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Añade el autor que dicha estrategia es recomendable para el estudio de enfermedades como el cáncer mediante la aceleración del sistema inmunitario editando las células T del paciente. Por ende, concluye que el equilibrio entre el beneficio y el riesgo para tratar dichos trastornos es favorable a diferencia de las incógnitas de editar los embriones humanos (29).…”
Section: Introductionunclassified